HYDROCHEMISTRY AND HEAVY METAL DISTRIBUTION IN SURFACE WATERS AND SEDIMENTS FROM THE LAGOS LAGOON COMPLEX - OMOREGHA, J.K; OKEKE, E.G.; NKWOJI, J.A. (Nigerian Journal of Fisheries, 2024)
ABSTRACT Industrial wastes constitute a major source of heavy metal contamination in coastal waters. This study was carried out to assess the hydrochemistry and heavy metal distribution in surface water and sediments from selected sites in the Lagos lagoon complex. Water and sediment samples were collected monthly between June and November 2021 from five sampling stations, and analysed in the laboratory following standard methods. The result showed that heavy metal concentration in water was lower than WHO standards. The metals, arsenic, iron, and nickel exhibited significant (P<0.05) spatial variation in sediments. The highest and lowest concentrations of arsenic and nickel in sediments were observed at Badagry and Langbasa respectively; while Fe was highest in Langbasa and lowest in Badagry. The highest and lowest values for all physicochemical water parameters were recorded at Bayeku and Badagry respectively, except turbidity and carbon dioxide. Conductivity, total dissolved solids, turbidity and total hardness at Bayeku and Langbasa exceeded WHO standard. The findings from this study emphasise the need for regular monitoring of the Lagos Lagoon Complex